Relationship Between Nurse Credentials and Nurse Performance at Mitra Sejati Hospital 2022 - Susy Hariaty; Dahlia Purba; Yuni Ramadhani (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to determine the relationship between the Implementation of Nurse Credentials and Nurse Performance at Mitra Sejati General Hospital. This research is descriptive correlation with cross sectional approach. The population of this study were all nurses working at Mitra Sejati General Hospital with a total of 160 people. The sampling technique used is a non-probability sampling method with purposive sampling. Data collection was carried out using a questionnaire. The statistical tests used were univariate and bivariate, namely the frequency distribution and the Spearman Rank (Rho) test with a significant level of 5%The research results showed that the results of the study showed that the majority of respondents had good Nurse Credentials, 22 respondents (55.0%), most of the Nurses' Performance was good, 21 respondents (52.5%). Based on bivariate data analysis of Nurse Credential Implementation and Nurse Performance using the Spearman Rank test (Rho) with a significance level of 5%, it was found that the p value <α 0.000 ≤ 0.05 means that there is a significant relationship between Nurse Credential Implementation and Nurse Performance with degree strength a strong relationship of 0.745. From the results of this study it is suggested to the Director that it is necessary to maintain and always provide direction to members of the medical committee regarding the management of credentials carried out by the medical committee.